2008
DOI: 10.1093/hmg/ddn060
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the CD36 gene associate with the metabolic syndrome and high-density lipoprotein cholesterol

Abstract: A region along chromosome 7q was recently linked to components of the metabolic syndrome (MetS) in several genome-wide linkage studies. Within this region, the CD36 gene, which encodes a membrane receptor for long-chain fatty acids and lipoproteins, is a potentially important candidate. CD36 has been documented to play an important role in fatty acid metabolism in vivo and subsequently may be involved in the etiology of the MetS. The protein also impacts survival to malaria and the influence of natural selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
168
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 53 publications
14
168
1
Order By: Relevance
“…The most significant promoter SNPs identified to influence CM levels and TG clearance (rs1931694, rs13228738, rs3211842) are in strong LD with variants previously associated with MetS or coronary artery disease (22,48,49). Similarly, the 3′UTR variant, rs7755, identified to associate with LDL and to trend with higher CM remnants has been CD36 transcriptional regulator (Fig.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The most significant promoter SNPs identified to influence CM levels and TG clearance (rs1931694, rs13228738, rs3211842) are in strong LD with variants previously associated with MetS or coronary artery disease (22,48,49). Similarly, the 3′UTR variant, rs7755, identified to associate with LDL and to trend with higher CM remnants has been CD36 transcriptional regulator (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Earlier genetic studies linked CD36 to fasting lipids (21, 48), MetS (22,(49)(50)(51), and stroke risk (44). However, information related to the role of the gene in postprandial lipid metabolism, which plays an important role in etiology of MetS and cardiovascular disease, remains limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allelic variation within the putative receptors that govern fatty acid taste (that is, within the genes that regulate GPR40, 120 and CD36) have already been established, [19][20][21] however, their association to taste remains unknown and these association will need to be investigated in subsequent studies. Interestingly, attenuated taste sensitivity to monosodium glutamate has recently been reported among OB women.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, complete deficiencies of Cd36 were reported in humans (Yamamoto et al, 1994;Kashiwagi et al, 1996) and a murine model featuring complete knockout of Cd36 is available (Febbraio et al, 1999), models carrying the 'incomplete' type of mutation may relevantly represent the more subtle functional consequences of common polymorphisms in human Cd36 gene. Actually, several single-nucleotide polymorphisms in the human Cd36 gene were recently associated with lipid levels, metabolic syndrome (Love-Gregory et al, 2008;Noel et al, 2010) or obesity (Bokor et al, 2010), although the latter has not been unanimously confirmed (Choquet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%